Reconstruction of the distal biceps tendon using triceps graft: a technical note - Thiago Medeiros Storti; Alexandre Firmino Paniago; Rafael Salomon Silva Faria (Revista Brasileira de Ortopedia)
ABSTRACT Rupture of the distal biceps brachii tendon typically occur in a contraction against resistance with the elbow in 90° of flexion. Chronic ruptures are uncommon and are complicated by tendon and muscle retraction and poor quality. Some reconstruction techniques have been described in the literature, with variations on the surgical exposures, type of graft (allo or autograft), graft donor site, and type of attachment to the radial tuberosity. The authors report the case of a patient presented a rupture of the distal biceps brachii tendon that took place five weeks earlier and, therefore, underwent reconstruction using autograft from the central strip of triceps tendon through double incision and fixation with anchors to the radial tuberosity. The use of the triceps brachii as autograft for reconstruction of chronic ruptures of the distal biceps had not yet been described in the literature. The authors have chosen to use it due to its biomechanical characteristics that qualify it as suitable for this procedure and because this is easier for collection, using the same operating field at the same joint, minimizing the negative effects of the donor area. After six months postoperatively, the patient has full movement arc and restoration of 96% of the flexion strength and 90% of the supination strength when compared with the contralateral limb. This procedure appears to be a good option for cases of chronic distal biceps rupture in older patients who have functional demand of supination.